Beyond Taste: The Impact of Sensory Design on Dining Interiors - Mayank Sethi; Deepti Pande Rana (International Journal of Environmental Planning and Development Architecture, 2025)
Dining experiences are increasingly recognized as multisensory events where the atmosphere of the environment significantly influences the overall perception of the meal. This study explores the impact of sensory design, encompassing visual, auditory, olfactory, tactile, and gustatory elements, on dining interiors. By examining the roles of color, lighting, acoustics, textures, and spatial arrangements, this study investigates how these factors contribute to customer satisfaction, behavior, and memory formation. Through an analysis of existing literature, theoretical frameworks, and detailed case studies of innovative restaurants, this study reveals the essential role of sensory design in transforming dining spaces into immersive, emotionally engaging environments that enhance the psychological and emotional experiences of diners.
Keywords: Dining experience; multisensory event; restaurants; sensory design